2005
DOI: 10.1002/jcp.20397
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 loss in MiaPaCa2 cells induces an altered cellular morphology and disruption in the organization of the actin cytoskeleton

Abstract: BRG1 and Brahma are critical and mutually exclusive subunits of the multi-constituent SWI/SNF chromatin remodeling complexes. These complexes play a key role in transcriptional regulation by dynamically altering chromatin architecture. Although the two proteins are very similar in structure, murine models demonstrate a clear dichotomy in BRG1/BRM function as heterozygous loss of BRG1 results in tumor development whereas homozygous loss of BRM does not. BRG1 and/or BRM protein is absent or disrupted in approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 50 publications
5
34
0
Order By: Relevance
“…In that respect, it is worth mentioning that the SWI/SNF ATPase subunit has already been involved in the regulation of cell morphology and cytoskeleton organization (35,36). Indeed, NIH-3T3 cells expressing dominant-negative ATPase-deficient BRG1 exhibit a larger size and attachment area (35), an observation in agreement with the increased size of hSNF5/INI1-deficient MRT, 293T, or MCF7 cells.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In that respect, it is worth mentioning that the SWI/SNF ATPase subunit has already been involved in the regulation of cell morphology and cytoskeleton organization (35,36). Indeed, NIH-3T3 cells expressing dominant-negative ATPase-deficient BRG1 exhibit a larger size and attachment area (35), an observation in agreement with the increased size of hSNF5/INI1-deficient MRT, 293T, or MCF7 cells.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, NIH-3T3 cells expressing dominant-negative ATPase-deficient BRG1 exhibit a larger size and attachment area (35), an observation in agreement with the increased size of hSNF5/INI1-deficient MRT, 293T, or MCF7 cells. Similarly, pancreatic adenocarcinoma cells, in which the expression of BRG1 was inhibited, exhibit a change in hSNF5/INI1 Inhibits Migration www.aacrjournals.org morphology and alterations of the actin cytoskeleton organization (36). Although they were not studied in the aforementioned reports, it will be of strong interest to document whether RhoA activation and altered cell motility are common features of the various systems with loss-of-function alterations of subunits of the SWI/ SNF complex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown that BRG1 loss induces an altered cellular morphology and disruption in the organization of the actin cytoskeleton (20), and mutations in the SWI/SNF complex resulted in changes in cell size and attachment area (21). Our results suggest that ADNP functionality plays a role in these changes.…”
Section: Discussionsupporting
confidence: 59%
“…4 By knocking down BRG1 expression in the BRM deficient MiaPaca2 cell line using shRNA, they observed that loss of SWI/SNF complex activity resulted in a dramatic change in cellular morphology accompanied by altered actin cytoskeletal organization. 5 Similar observations were made in a HeLa cell derivative D98oR. Knockdown of either BRM or BRG1 alone by stable expression of RNA did not apparently affect cellular morphology.…”
Section: Genetic and Epigenetic Determinants Of Tumor Progressionsupporting
confidence: 67%